Regulations and media literacy education on online sexual information: A Japanese perspective - Mayuko Watanabe (International Telecommunications Society (ITS), 2011)
This paper presents a Japanese perspective on measures against online sexual informaiton. A research queistion is set on what kinds of measures are required in order to protect youth from the harmful influence of online sexual informaiton. The paper firstly examines measures initiated by both national and local governments as well as by cell phone carriers, and secondly explores how to protect youth from potential online sexual dangers toward them. Lastly, the paper investigates the impact of online sexual information on Japanese young people's behaviors and values in comparison with that of other countries in an attempt to provide the basis for accurate measures. The results of the research found that online sexual information has some significant impact on young people, including the increase of the curiosity for sexual crimes.
Keywords: 330; Media literacy; Internet education; Mobile communications; Contents regulation; Harmful information; Child porngraphy